Salience of Somatosensory Stimulus Modulating External-to-Internal Orienting Attention - Peng, Jiaxin; Chan, Sam C. C.; Chau, Bolton K. H.; Yu, Qiuhua; Chan, Chetwyn C. H. (Frontiers in Human Neuroscience, 2017)
Shifting between one’s external and internal environments involves orienting attention. Studies on differentiating subprocesses associated with external-to-internal orienting attention are limited. This study aimed to reveal the characteristics of the disengagement, shifting, and reengagement subprocesses by using somatosensory external stimuli and internally generated images. Study participants were to perceive nociceptive external stimuli (External Low (EL) or External High (EH)) induced by electrical stimulations (50 ms) followed by mentally rehearsing learned subnociceptive images (Internal Low (IL) and Internal High (IH)). Behavioral responses and EEG signals of the participants were recorded. The three significant components elicited were: fronto-central negativity (FCN; 128–180 ms), fronto-central P2 (200–260 ms), and central P3 (320–380 ms), which reflected the three subprocesses respectively. Differences in the FCN and P2 amplitudes during the orienting to the subnociceptive images revealed only in the EH but not EL stimulus condition are new findings. The results indicated that modulations of the disengagement and shifting processes only happened if the external nociceptive stimuli were of high salience and the external-to-internal incongruence was large. The reengaging process reflected from the amplitude of P3 correlated significantly with attenuation of the pain intensity felt from the external nociceptive stimuli. These findings suggested that the subprocesses underlying external-to-internal orienting attention serve different roles. Disengagement subprocess tends to be stimulus dependent, which is bottom-up in nature. Shifting and reengagement tend to be top-down subprocesses, which taps on cognitive control. This subprocess may account for the attenuation effects on perceived pain intensity after orienting attention.